Chromosomal organization of retrotransposon Rex1 in Astyanax species (Characiformes, Characidae). Issue 1 (2nd January 2018) - Pessenda, Gabriela; Piscor, Diovani; Silva, Edson L. da; Centofante, Liano; Parise-Maltempi, Patricia P.
Abstract: The cytogenetic studies of retrotranposons Rex have been characterized in several fish groups, including species of the Astyanax genus. This group presents an extensive variability in their karyotype, with diploid numbers of 2 n = 52, 50, 48, 46 and 36 chromosomes. Thus, the aim of this study was to evaluate the distribution of the retrotransposable element Rex 1, in six Astyanax species, with different diploid numbers. The species analyzed were Astyanax altiparanae (2 n = 50), Astyanax asuncionensis (2 n = 50), Astyanax eigenmanniorum (2 n = 50), Astyanax marionae (2 n = 48), Astyanax fasciatus (2 n = 46) and Astyanax schubarti (2 n = 36). Rex 1 was dispersed in the Astyanax species, suggesting that these retrotransposons play important role in genome evolution.